Arsenic trioxide induces apoptosis of human gastrointestinal cancer cells - Ma, Zhi-Bin (Baishideng Publishing Group Co., Limited, 2014)
AIM: To investigate the changes in apoptosis in gastrointestinal cancer cells from patients with gastrointestinal cancers treated with arsenic trioxide (As(2)O(3)); and to study the possible molecular mechanisms of such changes by detecting the expression levels of p53 and Bcl-2. METHODS: Twenty patients with gastrointestinal adenocarcinoma based on endoscopic and biopsy findings (ten patients with gastric cancer and ten patients with colorectal cancer) who received treatment in our hospital between August 2007 and December 2008 were included in this study. None of the patients had received anti-tumour agents prior to As(2)O(3) treatment. As(2)O(3) was administered intravenously at a dose of 0.01 g/d diluted with 5% glucose in normal saline for 2-3 h for 3 consecutive days before surgery. Morphological changes associated with apoptosis of gastrointestinal cancer cells were observed by light microscopy. Changes in the apoptotic index induced by As(2)O(3) were investigated using the terminal deoxynucleotidyl transferase dUTP nick end labelling method. Expression levels of p53 and Bcl-2 proteins in gastrointestinal cancer tissues were determined by immunohistochemistry. RESULTS: The apoptotic index of human gastrointestinal cancer cells was higher in cells from patients treated with As(2)O(3) than in those not treated (P < 0.05). p53 protein expression in gastrointestinal tissues was unchanged by As(2)O(3) (P > 0.05). However, Bcl-2 protein expression in gastrointestinal tissues was down-regulated by As(2)O(3) (P < 0.01). CONCLUSION: These results demonstrate that As(2)O(3) treatment in patients with gastrointestinal cancers can induce apoptosis in gastrointestinal cancer cells and down-regulate Bcl-2 protein expression.